Food insecurity and revolution in the Middle East and North Africa : agrarian questions in Egypt and Tunisia - Ayeb, Habib; Bush, Ray (Anthem frontiers of global political economy, 2019)
'Food Insecurity and Revolution in the Middle East and North Africa' examines the political economy of agrarian transformation with case studies of Egypt and Tunisia. It critiques the dominant tropes of food security offered by the international financial institutions and promotes the importance of small-scale family farming in developing sustainable food sovereignty.